Patient Preferences in Choosing a Primary Care Physician - Francis Mercado; Margaret Mercado; Nancy Myers; Michael Hewit; Nairmeen Awad Haller (SAGE Publishing, 2012)
Background and Aims : Studies have identified factors important to patients in consideration of a primary care physician (PCP). Few have explored relevant differences in choosing between family medicine (FM) and internal medicine (IM) physicians. The objective of this study was to identify differences in rating of factors perceived to be important to racially diverse FM and IM patients in the selection of a PCP, and to determine patient knowledge of PCP training. Settings, Design, Methods, and Material : This observational study used self-administered questionnaires to obtain information from adult participants at 2 continuity clinics, FM and IM. Participants rated 16 factors on their importance in selecting a PCP. Demographics and information regarding participants' knowledge of PCP training were collected. Statistical Analyses Used and Results : 857 surveys were completed. Data were analyzed using descriptive statistics, Student t test, χ 2 , and multivariate logistic regression. Sixty-five percent and 32% of participants were Caucasian or African American, respectively. Combined responses from both clinics revealed g ood patient care as the factor ranked highest in importance for selecting a PCP, followed by good communication skills . Forty-eight percent and 35% of FM and IM participants, respectively, did not know whether their PCP was trained in IM or FM. More than 50% of participants were not familiar with the scope of their physicians' practice. Conclusions : Our results suggest that good patient care and communication are similarly important to all patients, regardless of race. Practices should maintain focus on these qualities, as well as on patient education regarding the relevant differences between FM and IM physicians. Results from this study are consistent with prior research on these issues in more racially homogenous populations.